Antecology and seed biology of false chestnut (Aesculus hippocastanum L) under thermal conditions - Choriyev Bakhodir Mamarajabovich (Genius Journals, 2022)
This article provides information on environmental protection activities in our republic, false chestnut, the anteecology and seed biology of false chestnut (Aesculus hippocastanum L) in Termiz conditions.
Keywords: Environment; false chestnut; bark; seed